2017
DOI: 10.1038/s41598-017-17522-8
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting energy from low-frequency excitations through alternate contacts between water and two dielectric materials

Abstract: Recent studies have demonstrated the benefits of water-dielectric interfaces in electrostatic energy harvesting. Most efforts have been focused on extracting the kinetic energy from the motions of water drops on hydrophobic surfaces, and thus, the resulting schemes inherently prefer cases where the water drops move at a high speed, or vibrate at a high frequency. Here we report a method for directly harvesting ambient mechanical energy as electric potential energy through water droplets by making alternate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In striking contrast to conventional design limited by interfacial effect, such a process exhibits a signature of bulk effect, leading to an increase in electrical outputs by several orders of magnitude. In spite of the boosted output performance, the transient output of this droplet‐based electricity generator is in the format of pulse, and typically has a duration time of several milliseconds, which is susceptible to low average electrical output 27‐36 . Although the average electrical output can be improved by increasing the frequency of liquid droplet impinging through reducing the empty interval between two neighboring pulses, an undesirable situation arises when the droplet falling on the surface could not be shed away immediately.…”
Section: Introductionmentioning
confidence: 99%
“…In striking contrast to conventional design limited by interfacial effect, such a process exhibits a signature of bulk effect, leading to an increase in electrical outputs by several orders of magnitude. In spite of the boosted output performance, the transient output of this droplet‐based electricity generator is in the format of pulse, and typically has a duration time of several milliseconds, which is susceptible to low average electrical output 27‐36 . Although the average electrical output can be improved by increasing the frequency of liquid droplet impinging through reducing the empty interval between two neighboring pulses, an undesirable situation arises when the droplet falling on the surface could not be shed away immediately.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this design is generic and simple, manifesting strong compatibility with advanced devices for hydrodynamic energy harvesting in a wide spectrum of forms. [ 181–183 ]…”
Section: Hydroelectric Effectmentioning
confidence: 99%
“…Studies of water have shown the potential of water-dielectric interfaces (as seen with chloride and water in plasma flow and cellular membranes) in electrostatic/potential energy harnessing and harvesting [8]. Recent cellular studies have also suggested that water and molecular attractions may play significant roles in the harnessing of energy components such as kinetic and potential bio-energy at the interface of cell membranes and in plasma flow [9][10][11][12][13]. Water that resides adjacent to hydrophilic surfaces/membranes appears to have defining characteristics that differ from bulk/free water (outside membranes and in the environment) and these unique features may correlate to the capacity to use magnetic attraction to harness energy and facilitate flow and movement of ionic solutions within plasma and across cell membranes [9,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Could viscosity that is not included in the Bernoulli equation by Johann Bernoulli be a significant component of the actual harnessing of magnetic energy in fluid flow in biological systems? It is known that a magnetorheological fluid becomes thicker and more viscous when subjected to a magnetic field [10]. The influence of diamagnetic copper on the generation of a.…”
Section: Introductionmentioning
confidence: 99%